Associations between the triglyceride–glucose index and the risk of heart failure in patients undergoing maintenance hemodialysis: a retrospective cohort study - Zhang, Qiuyue; Zhou, Kai; Li, Yuchen; Dong, Wen; Sun, Yimiao; Wu, Hui; Qiu, Xiaonan; Liu, Zhiyuan; Zhang, Ying (Frontiers in Endocrinology, 2025)
BackgroundAlthough the triglyceride-glucose (TyG) index levels have been shown to be a reliable predictor of major adverse cardiovascular events (MACE), few studies have investigated their association with heart failure (HF), especially in patients on dialysis. We therefore aimed to investigate the relationship between the TyG index and the incidence of HF in patients undergoing maintenance hemodialysis (MHD).MethodsA total of 183 participants who underwent MHD in the Blood Purification Center of the Affiliated Hospital of Xuzhou Medical University from September 2008 to October 2023 were included and followed up until March 2024. The TyG index was calculated as ln [fasting triglycerides (mg/dL) × fasting blood glucose (mg/dL)/2]. Participants were divided into two different groups according to the TyG index. The primary endpoint of this study was newly diagnosed HF events during the follow-up period. Cox proportional hazard models were used to examine the association between the TyG index and the risk of incident HF. To assess the dose-response relationship between TyG index and risk of HF, restricted cubic spline analysis was used.ResultsAmong the 183 participants, there were 61 incident cases of HF during a median follow-up period of 57 months. In comparison to the group with a lower TyG index, participants with a higher TyG index had a higher risk of HF (HR=2.590, 95%CI=1.490-4.500), regardless of whether a variety of potential confounders were adjusted. The association between TyG index and HF (P for non-linearity > 0.05) was confirmed by restricted cubic spline analysis.ConclusionThe TyG index was positively associated with the risk of incident HF in patients undergoing MHD, which indicates that the TyG index might be useful to identify people at high-risk for developing HF.